(untitled) (Revista Contexto & Educação, 2024)
This article aims to understand the role of the educational director as the governor who conducts his/her own action and the action of others. Based on Benincá (2010) and Foucault (2004; 2014), it explores the concepts of power, director, governor. It also reflects on the classical text and its ability to provoke the apprehension of new meanings and connections, resulting from the rereading and the context in which it is read. The article has three parts. First, it focuses on the concept of power in Foucault, recognizing its exercise as a relationship, which determines the action of one over the other. Afterwards, it deals with the relations and the pedagogical-subjects that inhabit school, addressing the meanings attributed by Foucault to the concept of subject. Still, with Benincá, the essay discerns subject and object: the first one, as someone capable of establishing a power relationship with himself/herself and with others; the second one, in contrast, as someone passive and indifferent. Finally, the article intertwines the researched concepts to reflect on the school director and his/her conduction, considering the ethical sense that it can assume. With such interpretative procedure, ultimately, the contribution that the classical text brings to the contemporary school director is analyzed, taking into consideration his/her mission to foster pedagogical-subjects, capable of freely self-determination.